Stress, personality, and their related factors of stress among female bus drivers of Bangkok Mass Transit Authority. - Mekrangsiman, W.; Lalitanantpong, D. (Chulalongkorn Medical Journal, 2023)
Background : Stress is an important mental health problem; it is mostly caused by work. Female bus drivers are responsible for driving many times a day and faced with pollution. Sometimes passengers complain about their performances which further lead to stress. However, there have been no data about stress among female bus drivers. Objective : To study stress, personality, and related factors of stress among female bus drivers of Bangkok Mass Transit Authority. Design : A cross - sectional descriptive study. Setting : Bangkok Mass Transit Authority. Materials and Methods : Data were collected from 119 female bus drivers of Bangkok Mass Transit Authority. The measurements were demographic data questionnaire, personality test (Maudsley Personality Inventory) and Suanprung stress test. Chi - square test was used to examine associated factors with stress. Logistic Regression Analysis was used to determine the predictors of stress among female bus drivers. Results : The result of the study shows that the 119 female bus drivers had their mean age of 46.42 years old. They had moderate stress level (42.9 %), extravert and stable personality (46.2 %). Factors that statistically significantly associated with stress (p < 0.05) were smoking, alcohol drinking, sedative drug use, shopping, family relationship problems, relationship problems with bus managers and neurotic personality (Scale N). Two predictive variables of stress were sedative drug use (OR = 9.8) and neurotic personality (Scale N) (OR = 1.2). Conclusion : Most female bus drivers had moderate stress level. Almost half of female bus drivers had history of alcohol drinking. This study could be used to plan for stress management programs for female bus drivers so that they could work more effectively.